Affirmative action policies in graduate education: a state of the art (PerCursos, 2026)
This article analyzes affirmative action policies in stricto sensu graduate education through a qualitative State-of-the-Art study covering the period from 2012 to 2023. Data were collected from the CAPES Theses and Dissertations Catalog and the Brazilian Digital Library of Theses and Dissertations (BDTD), comprising academic research developed in graduate programs in Education in Brazil. A total of 19 studies (13 master's dissertations and 6 doctoral theses) were selected to understand how this topic has been addressed in Brazilian academic production. The findings indicate that the debate on affirmative action policies in graduate education intensified from 2018 onward, with a greater concentration of studies conducted in the Southeast region, highlighting research gaps in other regions, particularly Northern Brazil. The analysis also reveals the presence of historically underrepresented groups, including Black women and men, Indigenous peoples, Quilombola communities, persons with disabilities, and transgender and travesti individuals, as well as the recurrence of themes related to access, retention, academic trajectories, and policy implementation. It is concluded that the studies analyzed demonstrate the growing academic interest in affirmative action policies in stricto sensu graduate education while also pointing to the need for greater regional diversity and further research in this field.
Keywords: affirmative action; graduate education; underrepresented groups; knowledge production; state of the art